Synthesis and characterization of 2-pyridineformamide 3-pyrrolidinylthiosemicarbazone - Shakya, B.; Yadav, P. N. (Journal of Nepal Chemical Society, 2013)
Pyrrolidine-1-carbothiohydrazide was prepared by the transamination reaction of 4-methyl-4-phenyl-3-thiosemicarbazide with pyrrolidine in MeCN. 2-pyridineformamide 3-pyrrolidinyl-thiosemicarbazone (HAmPyrr) was synthesized by the reduction of cyanopyridine in the presence of pyrrolidine-1-carbothiohydrazide in MeOH with Na metal. The synthesized compound was characterized by elemental analysis, IR, 1H-NMR, 13C-NMR spectroscopy and ESI mass spectrometry. The prominent (M+1) peak (m/z) of HAmPyrr in the electron spray ionization mass spectrum was found at 250.09 which correspond to the molecular ion plus H. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9234 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 28-33 Uploaded date : 12/3/2013